Evaluating the Role and Efficacy of Cobenfy (Xanomeline and Trospium Chloride) in Schizophrenia Treatment - review - Michał Mazur; Katarzyna Żak; Katarzyna Michalak; Krystian Zukierski; Weronika Jarych; Aleksandra Pliszka; Hubert Jucha; Katarzyna Madyniak; Agnieszka Kluz (Quality in Sport)
Schizophrenia is a complex psychiatric disorder often resistant to dopamine-targeting antipsychotics. Cobenfy, a combination of xanomeline and trospium chloride, offers a novel approach by modulating muscarinic receptors while minimizing side effects. This review evaluates its efficacy and safety, particularly in treatment-resistant cases. Clinical trials show significant reductions in both positive and negative symptoms, positioning Cobenfy as a promising alternative.